Self-Medication With Over-the-counter Medicines Among the Working Age Population in Metropolitan Areas of Thailand - Chautrakarn, Sineenart; Khumros, Waraporn; Phutrakool, Phanupong (Frontiers in Pharmacology, 2021)
Background and Objectives: Self-medication with over-the-counter (OTC) medicines is becoming an increasingly popular practice around the world. The global prevalence rate of self-medication ranges from 11.2% to 93.7%, depending on the target population and country. However, there is a lack of data on the prevalence and practices of self-medication among the working-age population, particularly in Thailand's metropolitan areas. The current study describes the prevalence of self-medication practices, adverse drug reactions and severity, reasons for self-medication, and basic medication knowledge among people of working age in metropolitan areas in Thailand. Methods: We conducted an online cross-sectional study between December 2020 and January 2021. Descriptive statistics were used to analyze self-medication data. A chi-square test was used to assess the association between self-medication and sociodemographic characteristics. Results: This study found high prevalence of self-medication among the working-age population in metropolitan areas of Thailand (88.2%). The most commonly used drug groups were NSAIDs (34.8%) and antibiotics (30.2%). Minor illness and easy access to pharmacies were the most common reasons for self-medication. Almost half of the participants' illnesses (42.6%) for which they self-medicated were not always completely cured, necessitating treatment at a hospital or clinic. Although only a small number of participants (ranged from 0.6 to 6.6%) experienced adverse drug reactions as a result of self-medication, some had severe symptoms that disrupted their daily lives or required hospitalization. In terms of basic medication knowledge, we discovered that study participants misunderstood some antibiotic drug concepts. Conclusions: According to the study’s findings, it is recommended that more information about the risks of self-medication, drug adverse reactions, antibiotic stewardship, more supervision of the prohibition of over-the-counter drugs and selling practices, and adequate facilities for people's access to medical services be provided at the policy level.